2015
DOI: 10.1007/s00441-015-2301-x
|View full text |Cite
|
Sign up to set email alerts
|

Poly(lactic-co-glycolide) polymer constructs cross-linked with human BMP-6 and VEGF protein significantly enhance rat mandible defect repair

Abstract: We have previously shown that the combined delivery of mesenchymal stem cells (MSCs), vascular endothelial growth factor (VEGF) and bone morphogenetic protein 6 (BMP-6) induces significantly more bone formation than that induced by the delivery of any single factor or a combination of any two factors. We now determine whether the exogenous addition of VEGF and BMP-6 is sufficient for bone healing when MSCs are not provided. Poly(lactic-co-glycolic acid) (PLAGA) microsphere-based three-dimensional scaffolds (P)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
23
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 46 publications
0
23
0
Order By: Relevance
“…1619 However, when we delivered VEGF and BMP-6 to a criticalsized rat mandibular defect, substantial bone regeneration was not achieved and the new bone was poor quality. 20 …”
mentioning
confidence: 99%
“…1619 However, when we delivered VEGF and BMP-6 to a criticalsized rat mandibular defect, substantial bone regeneration was not achieved and the new bone was poor quality. 20 …”
mentioning
confidence: 99%
“…To elucidate the role of exogenously added VEGF and BMP-6 in the absence of exogenously added MSCs to enhance bone repair, we cross-linked PLAGA scaffolds to either VEGF or BMP-6, or both growth factors combined, and delivered the PLAGA-growth factor constructs to critical-sized mandibular defects in rats. Significant bone regeneration was observed only in the rats that received the scaffolds to which the combination of VEGF and BMP-6 were cross-linked (Das et al, 2014;submitted for publication). This shows that the presence of extracellular VEGF or BMP-6 alone is not sufficient to enhance osteogenesis, whereas the combined presence of VEGF and BMP-6 is likely to be beneficial for fracture repair.…”
mentioning
confidence: 99%
“…Few studies also tested the combination of VEGF with BMPs and demonstrated their synergistic effects during bone repair/regeneration (Curtin, Tierney, McSorley, Cryan & Duffy, ; Das, Fishero, Christophel, Li & Kohli, ; Peng, Usas, Olshanski, Ho & Gearhart, ). Conversely, other authors showed that the simultaneous release of BMP‐2 and VEGF did not increase bone formation over BMP‐2 alone (Patel et al., ; Young et al., ) or in comparison to a DBBM graft (Schmitt, Lutz, Doering, Lell & Ratky, ) and did not increase de novo bone formation when added to DBBM blocks (Schmitt et al., ).…”
Section: Resultsmentioning
confidence: 99%